Prone Position after Liberation from Prolonged Mechanical Ventilation in COVID-19 Respiratory Failure - Andrei Karpov; Anish R. Mitra; Sarah Crowe; Gregory Haljan (Critical Care Research and Practice)
Objective and Rationale. Prone positioning of nonintubated patients has prevented intubation and mechanical ventilation in patients with respiratory failure from coronavirus disease 2019 (COVID-19). A number of patients in a recently published cohort have undergone postextubation prone positioning (PEPP) following liberation from prolonged mechanical ventilation in attempt to prevent reintubation. The objective of this study is to systematically search the literature for reports of PEPP as well as describe the feasibility and outcomes of PEPP in patients with COVID-19 respiratory failure. Design. This is a retrospective case series describing the feasibility and tolerability of postextubation prone positioning (PEPP) and its impact on physiologic parameters in a tertiary intensive care unit during the COVID-19 pandemic. Setting and Patients. This study was conducted on patients with COVID-19 respiratory failure hospitalized in a tertiary Intensive Care Unit at Surrey Memorial Hospital during the COVID-19 pandemic. Measurements and Results. We did not find prior reports of PEPP following prolonged intubation in the literature. Four patients underwent a total of 13 PEPP sessions following liberation from prolonged mechanical ventilation. Each patient underwent a median of 3 prone sessions (IQR: 2, 4.25) lasting a median of 1.5 hours (IQR: 1.2, 2.1). PEPP sessions were associated with a reduction in median oxygen requirements, patient respiratory rate, and reintubation rate. The sessions were well tolerated by patients, nursing, and the allied health team. Conclusions. The novel practice of PEPP after liberation from prolonged mechanical ventilation in patients with COVID-19 respiratory failure is feasible and well tolerated, and may be associated with favourable clinical outcomes including improvement in oxygenation and respiratory rate and a low rate of reintubation. Larger prospective studies of PEPP are warranted.